Middle string quartets: opp. 59, 74 and 95 - Beethoven, Ludwig van. 1770-1827 (Dover miniature scores, 2001)
Considered by many the greatest musical challenges facing strings players, Beethoven´s quartets are regarded by music lovers the world over as supreme masterpieces of the genre.